Analisis Semiotika Representasi Kemiskinan Pada Film Sedeng Sang - Eben Ezer Hutabarat; Andri Prasetyo Yuwono (Lembaga Pengembangan Kinerja Dosen, 2024)
Sedeng Sang is a film that tells the story of the conflict between families who have different views on the continuation of their children's education, because of the family's lower class economic background. Poverty is still an obstacle for people to get access to proper education because the income that is considered to support life is very uncertain, as farmers use traditional tools. The aim of this film is to invite viewers to reflect on the social situation of underprivileged families as a reality that still occurs today. The films presented show various conditions of poverty through clothing, food, shelter, and work. The research carried out aims to analyze how poverty is present in the film Sedeng Sang. The semiotic theory developed by Roland Barthes was chosen because it is in accordance with the research objectives in obtaining the results of this research. This research also uses descriptive qualitative to obtain results and explain the research results to be achieved. This research produces an analysis of the representation of poverty in the film Sedeng Sang as well as Roland Barthes' theory as a method that displays denotative, connotative and myth.